Topographies of the Works of Artur Becker - Gajdis, Anna (Transfer. Reception Studies, 2019)
The article aims to present the topographies in the prose and essays of the Polish-German writer Artur Becker. Becker comes from Warmia and Masuria, and constantly returns to the land of his youth, which by modern literary scholars, following William Blake and Czesław Miłosz, is called ‘The Land of Nod’ or no-man's- land. Both the writer and his literary heroes resemble the mythological Odysseus, who returns to his homeland driven by longing. Artur Becker is an emigrant like Adam Mickiewicz and Czesław Miłosz, and he perceives his homeland through the prism of socio-political changes after 1989. Becker's essay writing promotes Polish culture and literature. Becker refers not only to well-known and respected Polish poets, but also acquaints the reader with the literary and translation output of less-known Polish authors.